2021
DOI: 10.2217/fca-2020-0154
|View full text |Cite
|
Sign up to set email alerts
|

Perclose Proglide Embolization As a Complication: Case Report and Review of Literature

Abstract: Background: Vascular closure devices have replaced mechanical compression for closure of femoral access sites after endovascular procedures. Case: We present an 87-year old male with symptomatic infrarenal aortic aneurysm measuring 4.8 cm presenting for elective endovascular repair of the aortic aneurysm. A Perclose ProGlide Suture-Mediated Closure was used for closure. The closure was complicated by a separation of the ProGlide device resulting in the migration of the footplate to the descending aorta. Correc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…7 An extensive search of literature regarding the incidence of breakage and embolism of Perclose devices yielded only two results. 8,9 In both the cases, the embolized device could be retrieved with snare, without any complication. Jahromi et al have reported thromboembolic stroke after percutaneous treatment of inadvertent subclavian artery placement of a CVC.…”
Section: Discussionmentioning
confidence: 98%
“…7 An extensive search of literature regarding the incidence of breakage and embolism of Perclose devices yielded only two results. 8,9 In both the cases, the embolized device could be retrieved with snare, without any complication. Jahromi et al have reported thromboembolic stroke after percutaneous treatment of inadvertent subclavian artery placement of a CVC.…”
Section: Discussionmentioning
confidence: 98%
“…Embolization of intravascular foreign bodies poses many risks for our patients including the development of perforation, septic complications, thrombosis, and obstruction in blood flow [ 10 ]. In the previous two cases of Perclose ProGlide embolizations, a snare retrieval approach was used to manage this complication [ 5 , 9 ]. In our case, the patient needed to go to the operating room emergently.…”
Section: Discussionmentioning
confidence: 99%
“…The Watchman device (Boston Scientific Corporation, Marlborough, Massachusetts, United States) works by closing the LAA so the procedure serves as a promising, safe, and effective alternative to OAC, overcoming disadvantages including the risk of major bleeding. Vascular closure devices (VCDs) like Perclose ProGlide™ Suture-Mediated Closure System (Abbott Laboratories Inc., Chicago, Illinois, United States) have largely replaced the use of mechanical compression in managing femoral access after Watchman device procedures [ 5 ]. The device has demonstrated excellent safety.…”
Section: Introductionmentioning
confidence: 99%
“…Where in S-VCD, failure can be due to suture tear or incomplete apposition of highly calcified walls, toggle-plug malapposition due to calcium can lead to failure of C-VCD [ 19 ]. On the similar terms, both categories of devices may lead to other complications including distal embolization of the plug (in C-VCD) or foot plate (in S-VCD) and can also lead to infections of the arterial or access site [ 39 , 40 , 41 ]. Some of these factors may be non-modifiable, such as age and gender, but the introduction of intravascular lithotripsy facilitated transfemoral TAVR [ 42 , 43 ] or the reduction in sheath sizes with newer devices [ 44 ] may play important roles in the reduction of poor outcomes in LBA and further delineate any differences in the outcomes of these two VCDs.…”
Section: Discussionmentioning
confidence: 99%